Inside Back Cover: Gold‐Triggered Uncaging Chemistry in Living Systems (Angew. Chem. Int. Ed. 41/2017). Issue 41 (23rd August 2017) - Pérez‐López, Ana M.; Rubio‐Ruiz, Belén; Sebastián, Víctor; Hamilton, Lloyd; Adam, Catherine; Bray, Thomas L.; Irusta, Silvia; Brennan, Paul M.; Lloyd‐Jones, Guy C.; Sieger, Dirk; Santamaría, Jesús; Unciti‐Broceta, Asier
Abstract : Thiols are ubiquitous in living systems where they bind strongly to gold surfaces and render interactions with other functional groups basically non‐existent. In their Communication on page 12548 ff., J. Santamaría and A. Unciti‐Broceta et al. describe heterogeneous gold catalysts that enable bioorthogonal uncaging (by O/N‐depropargylation) of clinically approved anticancer drugs in cancer cell culture, and the first intracranial activation of a bioorthogonal probe in a zebrafish.